กระบวนการตรวจสอบข้อเท็จจริงของข้อมูลข่าวสารในสื่อสังคมออนไลน์ของผู้สูงอายุ - สุทธิมนัส ชินอัครพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The study on the process of fact checking information and news on social media of the elderly holds the objectives of the study with the first objective explaining the process of the elderly fact checking information and news on online platforms and the second objective is to study the process of building an understanding of the process of fact-checking information and news on an online platform by elderly. This is a qualitative research using a phenomenological method research approach choosing a specific group of subjects and selecting test subjects from an online observation, collecting data from both subject groups. The first subject group is the elderly that is 60 years old and above that have experience with online platforms and have fact checked information with in depth interviews and observation with no interference with a total of 12 people while the second subject group are four experts on fact checking and four experts on the elderly in this group, a total of eight people. The method used is in depth interviews to collect data. Results of the study indicated that the process of fact checking information and news on online platforms by the elderly is a process that is done in two major steps as the following 1) Fact checking with elderly’s Internal source and if elderly still doubt they might for forward to the next process 2) asses information from external sources (External source) After the process of fact checking information, the researcher has found that the process after fact checking is debunking the information. The researcher analyzed information gained from in depth interviews with the elderly and found that factor that related to the fact checking process of the elderly was convenience , past careers health problems and knowledge from knowledgeable seminars and institutions. As for the ways to enhance knowledge on fact checking information and online platforms of the elderly is to use public figures to enhance knowledge in fact checking, arranging learning activities, seminars and having a classroom to build skills, promote with fun content and doesn’t emphasize the problems that are related to the elderly while maintaining and adjusting content on social media that is moderate.